A autoridade real dos Tudor na história da Inglaterra de David Hume (1485-1603) - Palassi Filho, Arlindo (2021)
This thesis proposes to reconstruct the history of royal authority in England from 1485 to 1603, taking as theoretical and interpretive support the historical writing of the Scottish Enlightenment David Hume. In volumes 3 and 4 of the History of England: from the invasion of Julius Caesar to the Revolution of 1688, David Hume offers the reader a narrative about the historical evolution of England from the beginning of modernity under the reign of the House of Tudor. The aim of this study is to investigate how Hume interprets in his work the process of strengthening real authority in the Tudor era (1485-1603). It was intended to outline how the English royal authority was retaken and operated by the Tudor dynasty that emerged after the Wars of the Roses (1455-1485). This research was organized in four chapters. In the first, in addition to highlighting the intelectual training of David Hume, we initially engaged in a historiographical debate about Hume’s historical work. In the second, we present the context of elaboration of the History of England and examine the phenomenon of European and Scottish Enlightenment. In the third and fourth chapter, we are engaged in analyzing authority during the reigns of Henry VII, Henry VIII, Edward VI, Mary I and Elizabeth I. The research aims to contribute to the understanding of Hume’s History of England, fostering a discussion about of authority in the Tudor era.